(untitled) (Economic studies journal, 2025)
This Study Aims to Analyze the Causes of The Liquidity Shortage Crisis in Libya by Examining the Impact of Selected Monetary and Financial Variables on Money Demand, With A Particular Focus on The Abolition of The Interest Rate by Legislative Authority In 2013 And Its Subsequent Economic Implications. The Interest Rate Is Considered a Fundamental Instrument for Steering the Economy Toward Equilibrium. The Study Employed the Cointegration Approach Using the Autoregressive Distributed Lag (ARDL) Model and The Bounds Testing Procedure. The Results Revealed the Existence of Both Short-Run and Long-Run Equilibrium Relationships Between Money Demand and The Explanatory Variables. These Findings Are Consistent with Economic Theory and The Realities of The Libyan Economy. Specifically, The Abolition of The Interest Rate Encouraged Depositors to Withdraw Their Savings and Seek Alternative Investment Opportunities, Which Led to An Increased Demand for Both Domestic and Foreign Currencies. Consequently, This Behavior Exacerbated the Liquidity Shortage in The Banking System, As Individuals Opted to Retain Cash Outside the Formal Financial Sector.